Forming Character Through Moral Education In Early Children At Al-Hasan Village Kindergarten Kedungpanji - sulis setyowati (LP3M STAI MA'ARIF MAGETAN, 2023)
Children are the next generation of families and nations, need to get a good education so that their potentials can develop rapidly, so that they will grow into human beings who have strong personalities and have various kinds of abilities and skills that are useful. Therefore it is important for families, educational institutions play a role and are responsible for providing various kinds of stimulation and proper guidance so that a formidable next generation will be created. who hit his friend. The purpose of this study was to provide an understanding of character, moral education and the implementation of character building with moral education in early childhood at al-Hasan Kindergarten, Kedungpanji Village, Adapum. This research uses a type of qualitative research, data obtained by using interviews, observation , and documentation. The analysis used is to use the concepts provided by Miles & Huberman including: data reduction, data display and conclusion/verification. Character education is a process of planting and directing so that students are able to become fully human and have character in various dimensions. character education should also be given when children enter the school environment, especially since play groups and kindergartens. Development in early childhood is influenced by two factors, namely internal factors or internal factors and external or external factors. The formation of character with moral education carried out in Al Hasan Kindergarten includes the habituation of praying behavior in children in AL-Hasan Pulorejo Kindergarten. The strategy carried out by the teacher has been carried out well, while the strategies carried out include the teacher always reminding and explaining children about the etiquette of praying, being a figure for children in praying and applying rewards and applying punishments. if a child commits an act of saying dirty words, hitting a friend or doing other disgraceful actions, the teacher will definitely reprimand him and if during the lesson there is a student who does not pay attention to the teacher's instructions and when he is reprimanded the student does not comply, the student will come home later than his friends .